Comparative Analysis of Urban and Rural Ecosystems in the Context of Suitability for Honeybees - Dariusz Gerula; Paweł Węgrzynowicz; Zbigniew Kołtowski (Applied Sciences)
The present study set out to compare the performance of honeybees maintained in urban and agricultural environments across various regions in Poland. A range of measurements and observations were used to assess overwintering, development, strength, swarming behaviour, honey yield, and Varroa destructor infestation in bee colonies in five towns and five surrounding villages. The rural apiaries were located 4.5–39.5 km away from the urban apiaries. The colonies were kept in wooden Dadant hives and were led by Apis mellifera carnica queens. The brood count and colony strength were assessed based on the Liebefeld method, while Varroa destructor infestation levels in the colonies were determined using icing sugar at the end of July. The urban apiaries exhibited significantly higher brood-rearing dynamics. Consequently, an increase in brood count in spring resulted in a significant increase in Varroa infestation levels in summer. In certain regions, urban apiaries exhibited higher honey production, though this was influenced by geographic location and the availability of bee forage. The significant variation in most traits, including honey production, was observed depending on the region. Variations between years in the study were observed in bee colonies overwintering, brood numbers in the pre-spring period, and bee population in summer. This may suggest the presence of differing weather conditions.